Araf suresi özelinde Kur'ân-ı Kerim'de istifham üslubu –nahiv ve delalet ilmine özgü bir çalışma - ALI, KHALEEL MOHAMMED (Fırat Üniveristesi, 2020)
Bu çalışmada 'Kur'ân-ı Kerim'de İstifham Üslubu Araf Suresi özelinde nahiv ve delalet ilmi verileri bağlamında değerlendirilmiştir. Bu çalışma önsöz, giriş, üç bölüm ve bir sonuçtan oluşmaktadır. Çalışmada öncelikle üslup ve soru kavramlarının tanımı yapılmış, ardından soru edatları, maksatları, i'rabları ve cevap şekillerinden bahsedilmiştir. Ayrıca kendisinde onbir soru edatı zikredilmiş olan Araf suresindeki bu edatların geçtiği ayetler ele alınmıştır. Bu ayetlerdeki soru edatları gramer ve anlam yönünden analiz edilmiştir. Bu soru edatlarının manalarını belirleyen bağlamlar betimsel ve analitik yaklaşıma uygun olarak incelenmiştir. Anahtar Kelimeler: Kur'ân-ı Kerim, Araf suresi, Soru, Gramer, Anlam.

This study entitled "The Interrogative Method in the Holy Qur'an includes a semantic grammatical study and Surat Al-Aaraf is a modal." This study is about studying the interrogative sentences and its methods in the Holy Qur'an Surah "Al-Aaraf" specifically. This study has a an introduction, preface, three chapters and conclusion. It starts with defining the method and interrogation and after that mentioning its tools, purposes, syntax and it's answers. And then showing the verses mentioned in Surat Al-Aaraf that included fifty-one questions, and it's analyses in terms of grammar and semantics, and the role of context in defining their meaning according to the descriptive and analytical approach. And it is concluded with what the study reached to a number of results. Key Words: The Holy Qur'an, Surat Al-A'raf, Interrogation, Grammar, Semantics
The interrogative method in the Holy Qur'an includes a semantic grammatical study and (Surat al-Aaraf is a modal)
Keywords: Din